Spectrally-Robust Image Payload Embedding in Audio Hosts Using Perceptual and Cryptographic Strategies - Sampada Vishwas Massey,Dr. Megha Mishra,Dr. Vishnu Kumar Mishra (Journal of Computational Analysis and Applications (JoCAAA), 2024)
This paper presents a comprehensive framework for robustly embedding compressed image payloadsinto host audio signals via transform-domain, perceptually adaptive, and cryptographically secure techniques